2017
DOI: 10.1080/15384101.2017.1295183
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytes induce proliferation of oligodendrocyte progenitor cells via connexin 47-mediated activation of the ERK/Id4 pathway

Abstract: The proliferative ability of oligodendrocyte progenitor cells (OPCs) varied markedly under different culture conditions. Astrocytes (ASTs) have been verified to play a major role in regulating the proliferation of OPCs through direct contact. However, the mechanisms have not been fully clarified. To investigate the effect and mechanism under AST and OPC co-culture conditions, we analyzed all connexins comprehensively in OPCs under OPC mono-culture, AST-secreted cell factor co-culture and AST-OPC direct-contact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 34 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…The evidence discussed in this review indicates that both oligodendrocyte-oligodendrocyte coupling (mainly mediated by Cx47 and Cx32 homotypic GJCs) and oligodendrocyte-astrocyte coupling (mediated by Cx47/Cx43 or Cx32/Cx30 pairs) play a pivotal role in forming a functional panglial syncytium supporting the buffering of extracellular K + and metabolic supply to axons. Although the available literature suggests that oligodendrocyte progenitors would not contribute to this functional syncytial network, their role could not be completely ruled out based on recent findings showing the coupling of OPCs with astrocytes through Cx47 (Liu et al, 2017; Xu et al, 2017). Future research will elucidate whether OPCs make part of this interconnected glial network.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence discussed in this review indicates that both oligodendrocyte-oligodendrocyte coupling (mainly mediated by Cx47 and Cx32 homotypic GJCs) and oligodendrocyte-astrocyte coupling (mediated by Cx47/Cx43 or Cx32/Cx30 pairs) play a pivotal role in forming a functional panglial syncytium supporting the buffering of extracellular K + and metabolic supply to axons. Although the available literature suggests that oligodendrocyte progenitors would not contribute to this functional syncytial network, their role could not be completely ruled out based on recent findings showing the coupling of OPCs with astrocytes through Cx47 (Liu et al, 2017; Xu et al, 2017). Future research will elucidate whether OPCs make part of this interconnected glial network.…”
Section: Discussionmentioning
confidence: 99%
“…6C-d). The MAPK signaling pathway in neurons, astrocytes, and microglia, when inhibited by the in vivo injection of U0126, impacted OPCs variably [73] . Moreover, OPC differentiation induced by the ERK inhibitor could not restore processes in chronic demyelination [74] .…”
Section: Proliferation-related Changes In Erk and Its Downstream Mole...mentioning
confidence: 99%
“…This has led to a growing in-depth research focusing on cellular and molecular mechanisms underlying neurodegeneration to increasingly counteract this phenomenon. In human and in experimental models, a number of Cx alterations are differently involved in the development of various neurodegenerative diseases so much so that they are considered important therapeutic targets (Belousov et al, 2017 ; CharvĂ©riat et al, 2017 ; Liu et al, 2017 ). Several independent studies have pointed out that onset and progression of homeostatic imbalances observed during neurodegeneration could be associated with a GJ-independent increased membrane permeability related to HCs activity in the CNS (Retamal et al, 2007 ; Orellana et al, 2010 ; Burkovetskaya et al, 2014 ).…”
Section: Gjs Hcs and Cxs: Role In Neurodegeneration And Neuroprotecmentioning
confidence: 99%